Modelling and Simulation of a Single Phase Grid Connected Using Photovoltaic and Battery Based Power Generation - Alias , Khamis; Mohamed, Azah; Shareef, Hussain; Ayob, Afida; Mohd Aras, Mohd Shahrieel (2013)
Microgrid is a part of the power distribution system which uses renewable energy based of power generation connected to the grid system. Multi energy power generation is composed of renewable energy systems including photovoltaic, wind turbine, energy storage and local loads. Testbed of a microgrid system is the technique to ensure stable operation during faults and various network disturbances in grid and islanding connected mode. In this paper the microgrid using renewable energy consist of a 3 kW photovoltaic, with 30 pieces of 12V for 100Ah battery bank, DC/DC converter, charge controller for battery, single phase DC/AC inverter and various loads (resistor, capacitor, inductor) are develop. The AC buses 240V voltage include with isolation transformer to simulate the grid voltage level by Matlab/Simulink software.